RANCANGAN ANIMASI PENYULUHAN MATA PELAJARAN MATEMATIKA DASAR BAGI CALON GURU YANG AKAN MENGAJAR KE DAERAH TERTINGGAL - CINDY ALIF; ACHMAD SYARIEF; IFA SAFIRA SAGIR (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Instructional media are useful in assisting students and teachers to accumulate understandings on knowledge. Further, instructional media may serve as learning tool for young teachers prepared to be dispersed on various under-developed areas in Indonesia. Based on this premise, the authors develop and design an animation on the know-how of teaching basic math for students at under-developed areas of Indonesia. The purpose of instructional media design is to provide illustrative action in teaching basic math with limited educational resources. In the design process, the authors employed combined data of observation, interview, literatures, and field notes to understand social reality of teaching basic math at school with limited available resources. Processed data is compared with learning theory to develop contents of instructional media. It is resulted in a prototype of animation as an instructional media, produced as visual narrative of learning basic math at Papua as a case of targeted area. The animation is one of the series of instructional media contents, others are Indonesian, English, Natural Sciences, Social Sciences, and Arts. Keywords: animation; basic mathematic; instructional media